PENGARUH SALES GROWTH, LIQUIDITY, FIRM SIZE, DAN PROFITABILITY TERHADAP CAPITAL STRUCTURE DENGAN TANGIBLE ASSET SEBAGAI VARIABEL KONTROL (Studi pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Aufa, Alhiqni Raya; Wahyudi, Sugeng (Diponegoro Journal of Management, 2024)
ABSTRACT This study was conducted to analyze the effect of sales growth, liquidity, firm size, and profitability as independent variables on capital structure as a dependent variable, and tangible assets as a control variable. The sampling method used was the purposive sampling technique. The number of samples used was 28 consumer goods companies listed on the IDX in 2016-2020. Testing the hypothesis of this study using multiple linear regression with the IBM SPSS Statistics 25. The results showed that the variable sales growth had an insignificant negative effect on the debt-to-equity ratio variable. The variable current ratio and return on assets has a significant negative effect on the variable debt to equity ratio. The firm size variable has a significant positive effect on the debt-to-equity ratio variable. As a control variable, tangible asset has a good function in controlling the effect of independent variables on dependent variable